The Utilisation Of Hadith In Quranic Criticism - Muhammad Arif Musa; Khairul Anuar Mohamad; Ahmad Sanusi Azmi; Adnan Mohammad Yusoff (Universiti Sains Islam Malaysia, 2024)
The Sunnah contains of Qurʾānic explanation. It stands as the second most reliable interpretation of the Qur’ān. Qurʾānic critics has claimed that the Qur’ān consist of irreconcilable contradictory verses and the said notion might lead to rebuttal and rejection. Current contradiction claims differ from past claims. Current Qurʾānic critics are referring to Islamic sources to substantiate their criticism. On this matter, the Qurʾānic critics have cited a number of hadith to prove the inconsistency of the Quran. The research intend to study the contradiction claims in the Quran supported by the Sunnah as suggested by the Qurʾānic critics. The research is a qualitative study with analytical and critical approach. The research will study the assumed contradictory verses and the hadith used to support the contradiction claim. The research prove that current contradiction claims in the Quran has developed in a way that Qurʾānic critics has included Sunnah in their discussion. The inclusion of Sunnah has indeed made the claim seem to be more concrete. However, the research shows that the citation of Sunnah as evidence to the inconsistency of the Qur’ān is intangible. The assumed contradictory verses are in fact reconcilable and the citation of Sunnah do not corroborate the notion that the Qur’ān consist of contradiction. The research also suggest that any explanation by Islamic scholar on the assumed contradictory verses should include the evidences cited by the critics and on this occasion, the Sunnah.